The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.6007/ijarbss/v12-i9/15151
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Islamic Leadership's Effectiveness in Islamic-Based Institutions

Abstract: Background and Objective: Studies related to Islamic leadership focus on various aspects including the nature of a leader, the relationship between leaders and followers, and the positive implications of Islamic leadership on the organization. In order to ensure the effectiveness of Islamic-based institutions, it is very important to consolidate previous studies related to the effectiveness of Islamic leadership in Islamic-based institutions for future reference. Materials and Methods: This paper aimed to summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Islamic-oriented transformational leaders can drive employees' sense of self-integrity and Islamic work ethics via the four transformational leadership dimensions. This is because Islamic leaders would always encourage their followers to act appropriately and do good (Jabran & Sharfizie, 2022). Through role modeling, transformational leadership has a positive impact on employees' ethical behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Islamic-oriented transformational leaders can drive employees' sense of self-integrity and Islamic work ethics via the four transformational leadership dimensions. This is because Islamic leaders would always encourage their followers to act appropriately and do good (Jabran & Sharfizie, 2022). Through role modeling, transformational leadership has a positive impact on employees' ethical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Meraku (2017) has shown how leaders and their styles can significantly affect organizational effectiveness. In the context of Islamic-based institutions, Jabran and Sharfizie (2022) highlighted the importance of leadership in ensuring their success. Therefore, strong leadership is essential in these institutions.…”
Section: Introductionmentioning
confidence: 99%